ANALISIS PENERAPAN MANAJEMEN RISIKO TERINTEGRASI PADA BUMN: KAJIAN TEORETIS DAN REGULATIF TERHADAP KEBIJAKAN, PERENCANAAN, PELAKSANAAN, SERTA PEMANTAUAN RISIKO BERDASARKAN PER-05/MBU/09/2022 DAN PER-2/MBU/03/2023 DALAM MEWUJUDKAN TATA KELOLA YANG EFEKTIF DAN BERKELANJUTAN - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2026)
This study analyses the implementation of integrated risk management in State-Owned Enterprises (SOEs) through a theoretical and regulatory review of risk policies, planning, implementation, and monitoring based on PER-05/MBU/09/2022 and PER-2/MBU/03/2023 in order to achieve effective and sustainable governance. Using a qualitative-descriptive approach with content analysis of regulations, COSO ERM literature, ISO 31000, and SOE practice studies such as Pertamina, PLN, and Bank Mandiri, the study found that both regulations have created synergy between risk governance -Good Corporate Governance (GCG) synergy through Risk Appetite Statements, Risk Registers, and three lines of defence, which increased risk-adjusted ROE by up to 15% in mature entities. However, the main challenges include maturity level gaps (levels 2-5), risk aversion culture, human resource skill gaps, and Excel-based data fragmentation, which hinder universal implementation, despite the potential for a 20-30% reduction in material risk incidents through ERMIS and stress testing. The conclusion emphasises the need for a Risk Management Academy, Risk Maturity Scorecard, and progressive regulatory enforcement to transform SOEs into resilient ESG-based corporations that contribute to national economic stability.